Perbedaan Risiko Lingkungan Pekerjaan Di Kawasan Hutan Terhadap Kejadian Malaria Diantara Pasien Puskesmas Binuang - Maharso Maharso; Noraida Noraida; Jumiatul Aulia (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2017)
Abstract: Environmental Risk Differences Occupations In Forest Areas Against Malaria Incidence Among Binuang Puskesmas Patient. Tapin district in South Kalimantan also has forest areas and is malaria endemic. Binuang District is an area with the most malaria cases. In 2012 clinical malaria was found in 364 cases with 197 positive cases. The objective of this research is to know the difference of work environment risk in the historic area against malaria incidence. The study material was the medical record of all patients at Binuang Public Health Center of Tapin District, in the first tier of year 2016. The results showed that not every exposure with vector habitat (forest area) acted as risk factor to malaria disease status. Through Chi Square test, it is not proven that the type of forest encroachment work is related to malaria incidence, X2 count value is 1.875 smaller than X2 table (= 3,841), is at the acceptance of H0. However, gold miners (in forest areas) have a risk of contracting malaria by 29.13 times greater than non-gold counterparts. The calculation result of X2 is 41,76 bigger than X2 table (= 3,841), reject H0. For gold pending workers it is advisable to use insect repellent (repelent) and other mosquito-bitten protective gear while inside the gold repeating area. Keywords: Malaria risk; Gold pending; Malaria forest area.